Assessing point load strength in irregular phyllite via an equivalent area method. - Hong Zhang; Yong Cao; Qiang Luo; Wei Qi (PLoS ONE)
Obtaining intact cylindrical cores from soft, weathered rock is frequently challenging, making the point load test a preferred technique for quickly determining rock strength. This study critically evaluates two widely used point load strength calculations-the loading-span and equivalent-diameter methods-and presents an alternative "equivalent area method" founded on the ratio between the actual failure cross section and the minimum cross section. Irregular phyllite specimens spanning three levels of weathering (heavily, moderately, and slightly) are tested to analyze how shape factor (β) and loading span (D) affect the point load strength index (Is). Results show that the area factor has a skewed distribution, with median values increasing from 1.40 to 1.46 as weathering intensifies-substantially exceeding the 0.3 to 1.0 range in the loading-span method and surpassing the 4/π factor used in the equivalent-diameter approach. A recommended median area factor of 1.43 is therefore proposed. The measured Is decreases following a power-law trend as β and D increase, with weathering reducing the sensitivity of Is to β but not significantly altering its sensitivity to D. For heavily, moderately, and slightly weathered samples, the allowable β should be at least 0.4, 0.5, and 0.6, respectively, and the loading span should lie between 35 and 80 mm. Unlike the traditional loading-span and equivalent-diameter methods, the proposed equivalent area method incorporates a variable area factor ψ that accounts for the actual failure cross section in irregular specimens. This approach reduces scatter in test results and is particularly valuable for soft or weathered rock, where conventional cylindrical core preparation is infeasible. Through extensive testing on phyllite, we demonstrate that this method provides more stable estimates of point load strength and offers practical guidelines for specimen selection, making it highly relevant for geotechnical applications in weak-rock environments.